2011
DOI: 10.1007/s13209-011-0065-4
|View full text |Cite
|
Sign up to set email alerts
|

Are men and women-economists evenly distributed across research fields? Some new empirical evidence

Abstract: This paper analyzes the gender distribution of research fields in economics based on a new dataset of almost 1,900 researchers affiliated to top-50 economics departments in 2005, as ranked by Econphd.net website. We document that women are unevenly distributed across fields and test some behavioral implications from theories underlying such disparities. Our main findings are that the probability that a woman works on a given field is positively related to the share of women already working on that field (path-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
30
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 26 publications
(26 reference statements)
8
30
0
1
Order By: Relevance
“…As evaluators could be sympathetic to candidates working in their own research subject (see Hamermesh and Schmidt 2003;Bagues and Perez-Villadoniga 2009), if males and females tend to specialize in different subjects of research (as shown by Dolado et al 2012), then our finding that evaluators tend to favour candidates of their own gender could be due to a common subject effect.…”
Section: Associate Professormentioning
confidence: 80%
“…As evaluators could be sympathetic to candidates working in their own research subject (see Hamermesh and Schmidt 2003;Bagues and Perez-Villadoniga 2009), if males and females tend to specialize in different subjects of research (as shown by Dolado et al 2012), then our finding that evaluators tend to favour candidates of their own gender could be due to a common subject effect.…”
Section: Associate Professormentioning
confidence: 80%
“…According to the OECD, the observed gender wage gap in Spain was 11.8 % in 2009, clearly below the 15.8 % average for the 40 Gender segregation in tasks or specializations can also be observed even within a given occupation. Dolado et al (2012) study gender differences across research fields among academic economists. 41 For a discussion of this index, see Blau et al (2002).…”
Section: Wagesmentioning
confidence: 99%
“…There are several reasons for considering this hypothesis. First, there is evidence of gender segregation across different scientific subfields (Dolado, Felgueroso, and Almunia 2012;Hale and Regev 2014). If men and women tend to do research in different subfields and evaluators overrate the importance of their own types of research, the lack of female evaluators might be detrimental for female candidates PerezVilladoniga 2012, 2013).…”
mentioning
confidence: 99%